On the new genus Tropizodium (Araneae: Zodariidae), representing the femoral organ clade in Australia and the Pacific - Jocqué, Rudy; Churchill, Tracey B. (Zootaxa, 2005)
Tropizodium, a new genus of the spider family Zodariidae belonging to the “femoral organ clade”, is described. It contains three species all known from both sexes: T. peregrinum n. sp., the type species from northern Australia, and T. molokai n. sp. and T. trispinosum (Suman) n. comb., both from Hawaii. It is characterized by somatic characters such as the small intercheliceral triangle and the very small secondary eyes, and by a palp with a straight short embolus and an epigyne with extremely short entrance ducts. The genus is so far known only from the Hawaiian archipelago and northern Australia, extending the distribution of the clade and generating questions regarding its capacity for dispersal.